Mathematics E-learning Packets for Technical and Livelihood Education (TLE) Automotive Servicing - Tuazon, Jonathan C. (Future Science / FSH-PH Publications, 2024)
This study aimed to develop and evaluate Mathematics e-learning packets tailored for Technical and Livelihood Education (TLE) Automotive Servicing students at a public national high school, in the City Schools Division of Marikina for the School Year 2023-2024. The impetus for the study was based on the increasing number of learners who are having difficulty solving basic mathematical problems. The research addressed the following questions: (1) identifying Mathematics 9 topics suitable for e-learning packets based on literature review, (2) evaluating the developed packets by automotive and mathematics teachers according to DepEd guidelines concerning content quality, instructional quality, technical quality, assessment, visuals, and plan layout, (3) assessing any significant differences between the evaluations of the two groups of respondents, and (4) gathering comments and suggestions for improvement. Utilizing a descriptive research method, the study involved evaluations from 15 mathematics teachers and 15 automotive teachers from two public national high schools in Marikina City, Philippines. Data were analyzed using Weighted Mean and the Mann-Whitney U Test. Key findings include (1) prioritized topics under the Matatag Curriculum: perpendicular and parallel lines, relations and functions, quadratic functions and equations, direct and inverse variations, trigonometric ratios, and probability of simple events; (2) both groups rated the e-learning packets highly acceptable, with grand weighted means of 3.50 and 3.60, respectively; (3) no significant difference was found between the evaluations of the two groups; (4) respondents praised the packets' adequacy, organization, relevance, and interactivity, offering suggestions to incorporate more visuals, expand topics and activities, add video demonstrations, and involve industry professionals. In conclusion, the developed e-learning packets were well-received and deemed effective, with recommended enhancements aimed at further enriching the learning experience and bridging theoretical knowledge with practical application.